Mixed EHL numerical analysis and leakage experiment of skeleton reciprocating oil seal. Issue 4 (19th May 2021) - Yang, Hua-Lin; Li, Xiulong; Sun, Weiwei; Deng, Fang; Du, Jie
Abstract : Purpose: This paper aims to present the mixed elastohydrodynamic lubrication (EHL) model and obtain the leakage characteristics for the skeleton reciprocating oil seal. Design/methodology/approach: The model consists of a finite element analysis of the contact pressure, a fluid mechanics analysis of the fluid film, a contact analysis of the asperity contact pressure, a deformation analysis of the seal lip and an iterative numerical simulation process. Findings: Simulation results show that the leakage is in direct proportion to the seal roughness and speed, and in inverse proportion to the fluid viscosity. Comparisons with the experimental results verify the validity of the mixed EHL model. Originality/value: This study provides a helpful method to calculate the leakage of the skeleton reciprocating oil seal, which shortens its development cycles.